2013
DOI: 10.5535/arm.2013.37.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Plain Abdominal Radiograph as an Evaluation Method of Bowel Dysfunction in Patients With Spinal Cord Injury

Abstract: ObjectiveTo evaluate the usefulness of plain abdominal radiography as an evaluation method for bowel dysfunction in patients with spinal cord injury (SCI).MethodsForty-four patients with SCI were recruited. Patients were interviewed about their clinical symptoms, and the constipation score and Bristol stool form scale were assessed. The colon transit time (CTT) was measured by using radio-opaque markers (Kolomark). The degree of stool retention and the presence of megacolon or megarectum were evaluated using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Prior measurements of the degree of faecal loading have been exclusively described in children, and several systems have been developed to score both the amount of faeces and its localization in different colon segments[ 14 , 15 ]. The Leech-score is a reproducible tool for assessing faecal loading, with high intra-observer and interobserver agreement[ 13 , 16 - 18 ]. The plain abdominal radiograph has seldom been used in adults[ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior measurements of the degree of faecal loading have been exclusively described in children, and several systems have been developed to score both the amount of faeces and its localization in different colon segments[ 14 , 15 ]. The Leech-score is a reproducible tool for assessing faecal loading, with high intra-observer and interobserver agreement[ 13 , 16 - 18 ]. The plain abdominal radiograph has seldom been used in adults[ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Leech-score is a reproducible tool for assessing faecal loading, with high intra-observer and interobserver agreement[ 13 , 16 - 18 ]. The plain abdominal radiograph has seldom been used in adults[ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports show patient recall of bowel habits is sometimes inaccurate [ 24 ], so objective evaluation methods such as plain abdominal radiography and colon transit time are recommended [ 25 ]. Objective means of evaluation, such as constipation score, plain abdominal radiography, and colon transit time using Rome Criteria II used in the previous study [ 26 ], were presently adapted to estimate the effect of PF. A significant difference in postadministration was observed in constipation score, stool retention score, and colon transit time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plain abdominal radiography has the advantages of less cost, simple to perform, and less exposure to radiation. In 2013, Park et al [ 21 ] found that plain abdominal radiography for spinal cord injured patients had a significant correlation with CTT on constipation scores. They also reported that the interinvestigator consistency was high.…”
Section: Discussionmentioning
confidence: 99%